Simulation-Based Learning Impact on Medical Students. Interdisciplinary Formative Approach - Laverde, Andres Chiappe; Álvarez, Ricardo Andrés Novoa; Álvarez, Thiago Andrés Navarro; Parra, Sandra Liliana Navarro (Journal of Posthumanism, 2025)
Introduction: Simulation-based learning (SBL) is a valuable complement to the training of more qualified, competent and efficient professionals. Objective: To evaluate the scope and limitations of the implementation of a simulation-based learning environment with an interdisciplinary approach called “Simulation Clinic” from a teaching, curricular and evaluative perspective. Methods: Descriptive-exploratory study aimed at students of a higher education institution in 2022. A total of 272 students participated in the interdisciplinary SBL. Results: This strategy was approved by both students (4.28 average rating and 21% of students rated the activities with 5/5) and professors (4.56 average rating and one of them gave the maximum rating). There was evidence of an increase of 34.4% in the development of generic and specific competencies. The feasibility and effectiveness of the interdisciplinary SBL requires complex organizational, structural, technological and human factor adjustments for its adequate implementation in higher education institutions. Discussion: The results are in line with the objectives of several research studies that promote simulation-based teaching and learning leading to better performance in the clinical practices of medical and nursing students, while preparing students from other programs for professional practice.